A Knowledge Management System Conceptual Model for the Sorong COVID-19 Task Force - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Joseph Eliza Lopulalan (Society of Visual Informatics, 2020)
Sorong is a city located in the West Papua Province, Indonesia. It has a strategical location because it serves as the gateway of the West Papua Province. In 2019, its population has reached 247.084. Such condition has been deemed risky during the Covid-19 pandemic. The performance of the Sorong City Task Force for Covid-19 handling acceleration (Satgas Covid-19) had been considered ineffective by the citizens because it had not provided a system which would provide valid information regarding the Covid-19 progress in the city, resulting in worry and panic buying among the citizens. To overcome the problem, the knowledge possessed by the Sorong City Covid-19 Task Force should be developed into a Knowledge Management System (KMS). The implementation of the system had been expected to be able to optimize the documentation, dissemination and creation of knowledge as well as its evaluation. The KMS then was built to improve the performance effectiveness of the Sorong City Covid-19 Task Force in managing and disseminating knowledge regarding Covid-19 to the citizens. The methods utilized in this research were the qualitative method and the 10-step knowledge management roadmap. The research produced a conceptual model of KMS which could be utilized by the Sorong City Covid-19 Task Force.